The People Still Make the (Remote Work-) Place: Lessons from a Pandemic. (November 2021) - Nyberg, Anthony J.; Shaw, Jason D.; Zhu, Jing
The Journal of Management editorial team challenged us to consider how the COVID-19 pandemic impacted and altered the employer–employee relationship. In this guest editorial, we take stock of the pandemic-related lessons learned for human resources research and practice. We highlight three insights that many organizations made as the result of pandemic-related changes and describe how these lessons are likely to alter the employee–employer landscape for the foreseeable future. The lessons are (a) understanding that organizational communication practices should be authentic, continuous, and two-way in nature; (b) accepting that the virtual workforce brings unique challenges that do not yet have solutions; and (c) recognizing that success for stakeholders beyond just investors will require continual attention and intention. We also highlight needs and opportunities for future research that will inform theory and practice and lead to the betterment of organizations and society.